Genome wide simple sequence repeats development and their application in genetic diversity analysis in wax gourd (Benincasa hispida). (13th January 2022) - Hu, Qianmei; Wang, Haiping; Jiang, Biao; Zhu, Huayu; He, Xiaoming; Song, Pengyao; Song, Jiangping; Yang, Sen; Shen, Junjun; Li, Zheng; Hu, Jianbin; Sun, Shouru; et al.
Abstract: Wax gourd is one of the most important winter vegetables of the Cucurbitaceae family. There are only limited markers available for this crop and the draft genome of wax gourd provides a powerful tool for simple sequence repeats (SSR) marker development. In this study, we developed genome‐wide SSR markers from wax gourd genome and characterized their distribution and frequency of different motifs and repeats. A total of 52, 431 microsatellites from wax gourd genome were identified, of which 39, 319 SSR markers were developed. The 1152 non‐wax gourd SSR markers were selected from cucumber, melon, watermelon and pumpkin to test their transferability in wax gourd. The 580 SSR markers could be transferable in wax gourd, and 42 of them were detected with polymorphic in 11 tested accessions of wax gourd. In addition, 11 good polymorphic transferrable SSR markers and 21 SSR markers of wax gourd were selected to investigate the genetic diversity and population structure of 129 wax gourd accessions. One hundred twelve alleles were detected by these 32 SSR markers. The result of population structure showed that the 129 wax gourd accessions were divided into two main populations, and the genetic diversity analysis separated them into two clusters. The large number of wax gourd SSR markers developed in this study provides a valuable resource for genetic linkage map construction, molecular mapping, and marker‐assisted selection (MAS) in wax gourd.